2019
DOI: 10.1016/j.anr.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Practical Guidance for Knowledge Synthesis: Scoping Review Methods

Abstract: Scoping reviews are a useful approach to synthesizing research evidence although the objectives and methods are different to that of systematic reviews, yet some confusion persists around how to plan and prepare so that a completed scoping review complies with best practice in methods and meets international standards for reporting criteria. This paper describes how to use available guidance to ensure a scoping review project meets global standards, has transparency of methods and promotes readability though t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 12 publications
1
172
0
16
Order By: Relevance
“…The focus will be on those persons' needs and wants on the acronym PCC (participants, concepts, context). 53 The following research question was developed to define our search of the available knowledge and publications: "What does the literature say about Living Labs whose activities are dedicated to older adults with dementia, whether they live in the community or in nursing homes?" Specific objectives are:…”
Section: Aims Of the Scoping Reviewmentioning
confidence: 99%
“…The focus will be on those persons' needs and wants on the acronym PCC (participants, concepts, context). 53 The following research question was developed to define our search of the available knowledge and publications: "What does the literature say about Living Labs whose activities are dedicated to older adults with dementia, whether they live in the community or in nursing homes?" Specific objectives are:…”
Section: Aims Of the Scoping Reviewmentioning
confidence: 99%
“…27 Literature also indicates that scoping reviews are rigorous in their approach to providing rich and contextual details evidence of research activity in a particular area. 28 Despite the strengths, the lack of methodological quality assessment and quality of evidence grading even for empirical evidence minimises the ability of results from a scoping review to inform clinical decision-making. A recent critical review of the scoping review methods indicated that results of scoping reviews are not used to create recommendations for policy or practice.…”
Section: Open Accessmentioning
confidence: 99%
“…A recent critical review of the scoping review methods indicated that results of scoping reviews are not used to create recommendations for policy or practice. 28 Other important challenges in scoping reviews are the level of complexity across multiple stages 28 and practical issues related to the large corpus and the wide range of research literature. 25 Therefore, it is crucial to follow a sound methodological guidance or framework, 28 and to have a balance between breadth, comprehensiveness and feasibility.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations